Comparison Of Protection Laws Private Data In Indonesia, And The Philippines - Amiludin Amiludin; Siti Nurhalisa; Undang Prasetya Umara; Hidayatullah (Universitas Muhammadiyah Surakarta, 2024)
To compare private data protection regulations in Indonesia and the Philippines and understand dispute resolution related to private data cases in the two countries. This research method uses literature review studies derived from books and journals or articles that have been published. The research findings reveal a comparison between the Private Data Protection Act in Indonesia and the Philippines. It is noted that the Philippines already has an independent supervisory body, whereas Indonesia does not, despite the establishment of such an institution being regulated by the Private Data Protection Act number 27 of 2022. Additionally, the study aims to understand the dispute resolution mechanisms in case of private data theft in both Indonesia and the Philippines. This study compares the regulations of the Private Data Protection Act in Indonesia and the Philippines, focusing particularly on the establishment of an essential independent supervisory body that needs to be formed in Indonesia. Subsequently, the case resolution mechanisms through Alternative Dispute Resolution can be considered to eliminate practices that tend to be slow, complex, and expensive, as well as to stop corrupt practices in the courts, ensuring that the Indonesian community feels secure and protected. No specific research has been found that compares the regulations on Private Data Protection in Indonesia and the Philippines. This includes the establishment of an independent supervisory body to aid law enforcement authorities in identifying perpetrators of private data theft, providing education, and addressing public inquiries about private data. Additionally, the resolution of cases involving private data theft through alternative dispute resolution is deemed superior to the judicial route due to the frequent practices of being slow, complex, expensive, and corrupt, which can erode or even eliminate the trust of the Indonesian public in law enforcement authorities.